Influence of career identity on ethical leadership: sense-making through communication. Issue 9 (30th March 2020) - Ren, Shuang; Chadee, Doren
Abstract : Purpose: The widespread use of communication technologies and social media platforms such as the #ME TOO movement has amplified the importance for business leaders to demonstrate high standards of ethical behavior for career success. Although the concept of ethical leadership has been widely investigated, a theoretical framework from a career perspective does not yet exist. Design/methodology/approach: This study draws from sensemaking theory to argue that career identity salience shapes leaders' communication behavior to influence the extent to which they are perceived to be ethical by subordinates. We test our hypotheses using multisource data with a sample ( n = 337) of business managers. Findings: The results show that career identity salience has positive influence on communication competence, which positively influences ethical leadership. We further find that communication frequency positively moderates the relationship between communication competence and ethical leadership. Practical implications: The theoretical and practical implications that, motivated by their career identity, career-ambitious leaders can manipulate subordinates' perceptions of their ethical behavior are discussed along with suggestions for future research. Originality/value: To our knowledge, this is the first research to provide a career perspective on ethical leadership.